INFLUENCE BALANCED SCORECARD ON THE PERFORMANCE OF TELECOMMUNICATIONS COMPANIES (EMPIRICAL STUDY ON TELECOMMUNICATIONS COMPANIES IN 2020-2023) : INFLUENCE BALANCED SCORECARD ON THE PERFORMANCE OF TELECOMMUNICATIONS COMPANIES (EMPIRICAL STUDY ON TELECOMMUNICATIONS COMPANIES IN 2020-2023) - Ramadani, Rifki; Setyaningsih, Titik Agus (PENANOMICS: International Journal of Economics, 2025)
The formulation of the problem in this research is as follows: What is the influence of the Financial perspective, Customer perspective, Business Process perspective, Learning and Growth perspective partially on the performance of Telecommunication Companies? The aim of this research is as follows: To determine the influence of the Financial perspective, Customer perspective, Business Process perspective, Learning and Growth perspective partially on the performance of Telecommunication Companies. Research Results (1) The financial perspective has an insignificant negative effect on company performance. (2) The customer perspective has a significant positive effect on company performance. (3) The internal business process perspective has an insignificant negative effect on company performance. (4) The learning and growth perspective has an insignificant effect on company performance.